Evaluating the fit-effectiveness of fabric-based reusable face masks on 3D printed NIOSH headforms. Issue 19 (October 2022) - Stannard, Casey; Freeman, Charles; Strawderman, Lesley; Moore, Meagan; Newhauser, Wayne; Burch, Reuben; Black, Catherine; Saucier, David
Poor-fitting face masks can allow particles, including the coronavirus disease 2019 virus, to spread. Reproducible methods for fit testing face masks are scarce and many require sophisticated testing equipment. The purpose of this experimental research was twofold: (a) to develop a simple and reproducible method for assessing face mask fit at key facial areas; and (b) to utilize the method to examine the fit of various commercially available fabric-based face masks on different head shapes at key facial areas. The mask fit test method was developed to assess face mask fit in six key face mask/head correspondence areas: bridge of nose; cheek/area below the eyes (including the nasolabial fold); chin; ear loops; sides of mask near the ears; and sides of nose. Proper fit was indicated when no excessive tightness or gaping occurred. The mask fit test method was used to assess the fit of eight types of commercially available face masks on five three-dimensional printed headforms. The five headforms were created from the National Institute for Occupational Safety and Health standards for head shapes and sizes. Six evaluators utilized the mask fit test method to score the eight face masks on each headform. Overall, only two face masks had proper fit for the majority of the headforms. All other face masks exhibited loose or gaping fit. General trends included superior fit for larger headforms and poor fit for all face masks evaluated on the smaller phantom. Facial areas that commonly produced large gaps were the bridge of nose, cheeks, and sides of nose. Thus, this study recommends improved design and sizing of face masks to properly fit a larger segment of the population.